Evolusi Gaya Kepemimpinan dalam Era Digital - Aninditha Sulistya Putri; Faiza Rahma Wijaya; Nasywa Eka Anindya; Zulfa Dwi Fauzia; Susan Febriantina (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the evolution of leadership styles in the digital era influenced by rapid technological advancements. Using a literature review method based on library research, the study explores the shift from traditional leadership models to collaborative and technology-based leadership. The findings indicate that leaders in the digital era are required to master technology, drive innovation, and possess strong communication and interpersonal skills. Challenges such as rapid change, managing virtual teams, and data security are key focuses. By understanding these changes, leaders can create a more flexible, productive, and adaptive work environment.